Evaluation Of The Main Deck Maintenance System To Prevent Corrosion In KM. Tanto Aman - Brenhard, Mangatur T; Priambudi, Miko (IWTJ : International Water Transport Journal, 2023)
Corrosion that occurs on a ship is essentially a natural enemy for all sailors because the emergence of a corrosion on a ship can cause the loss of an iron so that it can endanger the crew of the ship itself and other people on the ship. Therefore the author would like to convey how to effectively eradicate the corrosion that occurs. Corrosion can be caused by two factors that greatly affect the rate at which corrosion occurs. These two factors are caused by human activity factors, such as lack of maintenance and cleaning on the ship. And the second factor is the influence of nature, such as high rainfall intensity, air temperature, and humidity.